Identity changes and the efficiency of reputation systems - Matthias Wibral (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
Reputation systems aim to induce honest behavior in online trade by providing information about past conduct of users. Online reputation, however, is not directly connected to a person, but only to the virtual identity of that person. Users can therefore shed a negative reputation by creating a new account. We study the effects of such identity changes on the efficiency of reputation systems. We compare two markets in which we exogenously vary whether sellers can erase their rating profile and start over as new sellers. Buyer trust and seller trustworthiness decrease significantly when sellers can erase their ratings. With identity changes, trust is particularly low towards new sellers since buyers cannot discriminate between truly new sellers and opportunistic sellers who changed their identity. Nevertheless, we observe positive returns on buyer investment under the reputation system with identity changes, and our evidence suggests that trustworthiness is higher than in the complete absence of a reputation system.
urn:nbn:de:bvb:19-epub-20930-9
Keywords: C91; D02; L14; 330; trust; reputation; identity changes